Study on Suitability of KOD DNA Polymerase for Enzymatic Production of Artificial Nucleic Acids Using Base/Sugar Modified Nucleoside Triphosphates - Satoshi Obika (Molecules, 2010)
Recently, KOD and its related DNA polymerases have been used for preparing various modified nucleic acids, including not only base-modified nucleic acids, but also sugar-modified ones, such as bridged/locked nucleic acid (BNA/LNA) which would be promising candidates for nucleic acid drugs. However, thus far, reasons for the effectiveness of KOD DNA polymerase for such purposes have not been clearly elucidated. Therefore, using mutated KOD DNA polymerases, we studied here their catalytic properties upon enzymatic incorporation of nucleotide analogues with base/sugar modifications. Experimental data indicate that their characteristic kinetic properties enabled incorporation of various modified nucleotides. Among those KOD mutants, one achieved efficient successive incorporation of bridged nucleotides with a 2′-ONHCH2CH2-4′ linkage. In this study, the characteristic kinetic properties of KOD DNA polymerase for modified nucleoside triphosphates were shown, and the effectiveness of genetic engineering in improvement of the enzyme for modified nucleotide polymerization has been demonstrated.